Creating the visitor-centered museum - Samis, Peter S (Routledge, 2017)
What does the transformation to a visitor-centered approach do for a museum? How are museums made relevant to a broad range of visitors of varying ages, identities, and social classes? Does appealing to a larger audience force museums to "dumb down" their work? What internal changes are required? Based on a multi-year Kress Foundation-sponsored study of 20 innovative American and European collections-based museums recognized by their peers to be visitor-centered, Peter Samis and Mimi Michaelson answer these key questions for the field. The book